Blood cellular changes associated with bacteremia and malaria co-morbidity among children in western Kenya - Ogulla, G.; Mwalimu, Stephen; Muturi, M.; Ouma, C. (Sciencedomain International, 2020)
Background: Malaria and bacteremia co-morbidity in children cause changes in blood cellular components. Complete blood count from children whose haemoglobin genotypes and bacteremia tests are not known, greatly influence clinical management and interpretation of the haematology results in resource limited healthcare facilities. Objectives: We investigated cellular components from children with bacteremia and malaria co-morbidity. We also analysed the haemoglobin genotypes and bacteria isolates from children with haemoglobin AA, SS and AS in western Kenya. Methods: A total number of 384 children were recruited and complete blood counts done with an automated cell counter. Microscopy was used to determine malaria infections, while bacteremia was determined by blood culture. The haemoglobin genotypes were analysed using the electrophoresis technique. Results: Children with haemoglobin AA and AS had elevated granulocyte counts. Most of the bacteria isolates were from children with malaria and haemoglobin AS. The bacteria isolated from blood culture included non-typhi salmonella, Escherichia coli, Enterobacter cloacae, Staphylococcus aureus, Listeria monocytogenes, Streptococcus pyogenes and Viridans. Salmonella species and staphylococcus aureus were the most prevalent bacteria isolates associated with bacteremia in children with haemoglobin AS and malaria positive. Conclusion: Children with Hb AS have higher chances of malaria and bacterial co-infection which leads to lymphocytopenia, erythrocytopenia and thrombocytopenia. Bacteria responsible for most of malaria co-infections in this region are Salmonella species and Staphylococcus aureus. The malaria and bacterial co-infection in pre-school children initiate differential cellular changes which should be investigated further.